2021
DOI: 10.1371/journal.pgen.1009573
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine mediates the crosstalk between LET-607 and DAF-16 stress response pathways

Abstract: Coordinated regulation of stress response pathways is crucial for cellular homeostasis. However, crosstalk between the different stress pathways and the physiological significance of this crosstalk remain poorly understood. In this study, using the model organism C. elegans, we discovered that suppression of the transcription factor LET-607/CREBH, a regulator of cellular defense and proteostatic responses, triggers adaptive induction of DAF-16-dependent stress responses. Suppression of LET-607 improves stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…A recent C. elegans study reported that the levels of unsaturated PCs are decreased in a long-lived C. elegans model. More importantly, the reduction of unsaturated PC species likely function in the endoplasmic reticulum (ER) to promote longevity by activating the ER-resident calcium channel, downstream calcium-sensitive kinases, and the transcription factor DAF-16 ( He et al, 2021 ), suggesting that specific unsaturated PCs may interact with membrane proteins to regulate longevity. The finding that reduction of unsaturated PC is beneficial for lifespan extension is consistent with the idea that low contents of unsaturated PCs may be a longevity signature.…”
Section: Phosphatidylcholinementioning
confidence: 99%
“…A recent C. elegans study reported that the levels of unsaturated PCs are decreased in a long-lived C. elegans model. More importantly, the reduction of unsaturated PC species likely function in the endoplasmic reticulum (ER) to promote longevity by activating the ER-resident calcium channel, downstream calcium-sensitive kinases, and the transcription factor DAF-16 ( He et al, 2021 ), suggesting that specific unsaturated PCs may interact with membrane proteins to regulate longevity. The finding that reduction of unsaturated PC is beneficial for lifespan extension is consistent with the idea that low contents of unsaturated PCs may be a longevity signature.…”
Section: Phosphatidylcholinementioning
confidence: 99%
“…As the empty liposomes are formed by lecithin (phosphatidylcholine), which is a constituent of biological membranes that has been demonstrated to modulate DAF-16 in C. elegans, we suggest that these factors contributed to increasing lipid in egg production as signaling and source of energy. [26,27,28] We found that the treatment with BGCE-loaded liposomes reduced the formation and area of the tumors in the third adulthood day (Figure 5a-b), attenuating the phenotype formation (Figure 5c, Figure S6) and increasing the lifespan of the worms (Figure 5d).…”
Section: Resultsmentioning
confidence: 85%
“…A curious finding was observed in the empty liposomes, which increased the number of eggs per worm. As the empty liposomes are formed by lecithin (phosphatidylcholine), which is a constituent of biological membranes that has been demonstrated to modulate DAF‐16 in C. elegans , we suggest that these factors contributed to increasing lipid in egg production as signaling and source of energy [26,27,28] …”
Section: Resultsmentioning
confidence: 89%
“…Apart from these local effects, the interaction of the lysosome with other intracellular calcium stores enables the transduction of the lysosomal calcium event to other subcellular compartments and to a global calcium event (75)(76)(77), which activates the longevity transcription factor DAF-16 via the calcium-dependent kinases PKC-2 and SGK-1 (68,69). Consistently, abnormal lysosomal calcium homeostasis is associated with aging-related diseases, such as Parkinson's disease and Alzheimer's disease (78)(79)(80).…”
Section: Sphingolipid Regulation Of Lysosomal Calcium: a Possible Rol...mentioning
confidence: 95%